A scoping review for designing a disability curriculum and its impact for medical students - Ali, Abdinasir; Nguyen, Julie; Dennett, Liz; Goez, Helly; Rashid, Marghalara (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2023)
Background: There is an increasing need for a standardized undergraduate disability curriculum for medical students to better equip students with the proper training, knowledge, and skills to provide holistic care for individuals with disabilities.Objectives: The aim of this scoping review was to better understand and analyze the current body of literature focusing on best practice for including disability curricula and its impact on undergraduate medical studentsResults: Three major components for designing a disability curriculum for undergraduate medical students were obtained from our analysis. The components were: (1) effective teaching strategies, (2) competencies required for disability curriculum, and (3) impact of disability curriculum on medical students.Conclusions: Current literature revealed that exposing medical students to a disability curriculum impacted their overall perceptions about people with disabilities. This allowed them to develop a sense of understanding towards patients with disabilities during their clinical encounters. The effectiveness of a disability curriculum is dependent on the extent to which these interventions are incorporated into undergraduate medical education.